Comparative proteomics and micro-RNA analysis of skeletal muscle cell small extracellular vesicles - Unique profiles in cells from severely obese individuals with type 2 diabetes versus normal glucose tolerance - Christiansen, Stian Forstrøm; Haug, Kari Bente Foss; Hussain, Misbah; Hussein, Abdille; Brusletto, Berit Sletbakk; Øvstebø, Reidun; Witczak, Oliwia; Aas, Vigdis (Frontiers in Physiology, 2025)
Type 2 diabetes (T2D) is associated with increased morbidity, mortality, and substantial healthcare costs. Peripheral insulin resistance, involving interconnected dysregulation of multiple organs, is considered a major driver of T2D. Extracellular vesicles (EVs) are suggested as mediators of this dysregulation based on their properties in intercellular communication. Given the role of skeletal muscle in glucose metabolism, the content of skeletal muscle-derived EVs may provide insights into mechanisms of T2D. To examine this, myotubes from severely obese female T2D donors and matched women with normal glucose tolerance (NGT) were cultured. Small EVs (sEVs) were isolated by differential centrifugation and filter columns and characterized by nanoparticle tracking analysis, flow cytometry, and transmission electron microscopy. The micro-RNA (miR) content of sEV was analyzed via Affymetrix microarray, while proteins were detected by LC-MS/MS. No group differences were found in sEV concentration, size, or EV-marker levels. In total, 495 proteins were detected in the sEVs, of which 55 were unique to the T2D group and 2 to the NGT group. Principal component analysis showed distinct clustering, demonstrating clearly different protein profiles. Quantification of the protein cargo revealed 194 proteins with significantly higher levels and 21 with significantly lower levels in the T2D group. While 208 miRs were detected, no significant group differences were observed. However, 40 miRs were unique to the T2D group and 5 to the NGT group. Pathway analysis of protein and miR data revealed associations with EV-related mechanisms such as exocytosis and protein homeostasis, as well as T2D-relevant pathways including some involved in glucose metabolism, inositol metabolism, and extracellular matrix organization. In conclusion, myotube-derived sEVs from severely obese female donors with or without T2D showed distinct proteome-profiles, however, no differences were observed in the miR content. Other sEV characteristics were similar between the groups.